Evaluating the effectiveness of problem-based learning in promoting rational prescribing among undergraduate medical students - Setu, Mohosina Sultana; Shajjad Hossain, M.; Ferdous, Zannatul; Al Amin, M. Mehedi Hasnat; Gupta, Akash; Hossain, M. Emran (International Journal of Research in Medical Sciences, 2025)
Introduction: Rational prescribing is a core competency for future physicians, but traditional pharmacology teaching often emphasizes factual recall rather than clinical application. Problem-Based Learning (PBL) is a student-centered approach that has been proposed to enhance problem-solving skills and rational prescribing. To evaluate whether a PBL-based pharmacology module improves knowledge transfer, problem-solving ability, and attitudes toward learning compared to conventional teaching. Methods: This interventional study included two groups of undergraduate medical students. The intervention group received a structured PBL module on drugs used in bronchial asthma, while the control group was taught through conventional lectures and tutorials. Both groups were assessed with problem-based multiple-choice questions on bronchial asthma (direct knowledge) and peptic ulcer (transfer of knowledge). Assessments were conducted at four weeks and again at two months. Student attitudes toward PBL were also collected via a structured questionnaire. Results: Students in the PBL group scored significantly higher than the control group in both assessments (p<0.01). While performance declined over time in both groups, PBL students consistently maintained superior outcomes. Feedback revealed positive attitudes toward PBL, with high ratings for problem-solving, motivation, teamwork, and overall satisfaction. Conclusion: PBL is more effective than conventional teaching in enhancing rational prescribing skills and student engagement. However, sustained practice and curricular integration are recommended to maintain long-term benefits.